Should I Stay or Should I Go? Founder Power and Exit via Initial Public Offering - Souitaris, Vangelis; Zerbinati, Stefania; Peng, Bo (Grace); Shepherd, Dean (Academy of Management Journal, 2020)
Founders can voluntarily exit their ventures via initial public offerings (IPOs). This study builds on power theory to develop and test a model of founder exit using a dataset of 313 founders from 177 entrepreneurial IPOs between 2002 and 2010. We largely find support for the model—a negative relationship between founder power and full exit. To capture the underlying mechanism of the power–exit relationship, we conducted two experiments in which we randomly assigned decision makers to either a high- or low-power condition. We find that decision makers in the low-power condition are more likely to use a full exit via IPO than those in the high-power condition, and that frustration mediates this relationship. However, founders can also engage in partial exits, including a managerial partial exit in which the founder leaves management but keeps ownership, and a financial partial exit in which the founder divests ownership but remains in management. We find that the negative relationship between founder power and exit is more negative for full exits than for partial exits. With this paper, we contribute to the literature on exit by identifying a novel mechanism—frustration—underlying power’s influence on the likelihood and type of founder exit.